PENGARUH GRIT TERHADAP PROKRASTINASI AKADEMIK PADA MAHASISWA TINGKAT AKHIR - Clara Felicia; Natalie; Clarissa Chrishella Simanjaya; Untung Subroto (STKIP Subang, 2025)
Final year students often face high academic pressure, especially in completing final assignments such as theses. This pressure can trigger academic procrastination behavior, namely the tendency to postpone completing important tasks. This study aims to determine the effect of grit, namely a combination of enthusiasm and perseverance to achieve long-term goals on academic procrastination in final year students. The study used a quantitative approach with a causal-comparative design. The measuring instruments used were the Grit-O Scale developed by Angela Duckworth and the Academic Procrastination Scale developed by Solomon & Rothblum, which were distributed online via Google Form. Participants in this study were 140 sixth semester students and above from various universities. The results of the analysis using the Pearson correlation test showed a strong and significant negative relationship between grit and academic procrastination (r = -0.638; p <0.05). This finding indicates that the higher the level of grit a student has, the lower their tendency to postpone academic tasks. Thus, developing grit can be an effective preventive strategy in reducing procrastination behavior, especially in final year students.